Strawberry Extract’s Effects on Enterococcus faecalis and Porphyromonas gingivalis Biofilms in vitro - Armelia Sari Widyarman; Stephanie Brigitta Widjaja; Erik Idrus (Faculty of Dentistry, Universitas Trisakti, 2017)
Background: Enterococcus faecalis (E. faecalis) and Porphyromonas gingivalis (P. gingivalis) are oral bacteria related to root canal infection and periodontal disease pathogenesis. Strawberries (Fragaria x ananassa) fruit are rich in vitamins and minerals, have antibacterial and antioxidant effects. Objective: This study investigated the inhibition effect of strawberry extract on monospecies and multispecies E. faecalis and P. gingivalis bacteria grown as biofilms in vitro. Methods: This study used E. faecalis ATCC 29212 and P. gingivalis ATCC 33277. It analyzed the effect of strawberry extract on bacteria biofilm formation using a biofilm assay on microplate wells. Five concentrations of strawberry extracts were used (100%, 50%, 25%, 12.5%, and 6.25%), and the inhibition effect was observed after a 1h, 3h, 6h, and 24h incubation period. Biofilms without the strawberry extract were used as the negative controls, and crystal violet and safranin (0.5%w/v) were used to count the biofilm mass. The biofilms grown on microplates were counted using an ELISA reader at 450 nm after 200 mL of 90% ethanol was added to attract the absorbed stain. The strawberry extract inhibition effectiveness on the biofilm formation of each bacterium tested was analyzed using one-way Anova, where p<0.05 was defined as a significant difference. Result: The strawberry extract inhibited the tested monospecies and multispecies bacteria biofilm formation. The optimal strawberry extract concentration for the inhibition of either monospecies biofilms was 100%. However, the optimal incubation time for the strawberry extract to inhibit the multispecies biofilm formation was 24h, which was the study’s biofilm maturity phase. Conclusions: The 100% strawberry extract concentration inhibited the formation of both the monospecies and multispecies E. faecalis and P. gingivalis biofilms. Future studies are needed to evaluate the potential of strawberry extract as an alternative dental therapy.